Towards Restorative-Based Corrections: An Alternative to Reduce Prison Overcrowding - Surbakti, Egy Aginta Syahputra; Fathoni, Achmad Robbi; Effendi, M. Firdaus Azhari; Suganda, Jecki; Putra, I Wayan Budi Pratama; Sigalingging, Frando Natanael (Reflection Journal, 2025)
This study examines the application of restorative justice as an alternative approach to addressing the persistent problem of overcrowding in Indonesian correctional institutions. Overcrowding driven by the dominant use of imprisonment—has undermined the rehabilitative function of prisons, increased health and security risks, and reduced the overall effectiveness of correctional programs. Using a library research method with a descriptive qualitative approach, this study analyzes legal frameworks, policy documents, and empirical research relevant to restorative justice and alternative sentencing. Literature searches were conducted through databases such as Sage, Elsevier, Cochrane Library, SSRN, and Google Scholar. Following a PRISMA-based selection process of 87 initial documents, 13 publications (2013–2025), including academic articles, policy reports, and statutory regulations, met the inclusion criteria. The findings indicate that restorative justice has significant potential to reduce incarceration rates through resolution mechanisms centered on healing, accountability, and social reintegration. However, its implementation in Indonesia remains constrained by limited human resources, a predominantly retributive legal culture, and weak inter-agency coordination. These findings underscore the need for stronger regulatory support, expansion of restorative mechanisms into the correctional stage, and data-driven evaluation to reduce overcrowding and advance a more humane and effective penal system.